Latvijas tranzīta attīstības perspektīvas Krievijai pievienojoties PTO - Kolberga, Diāna (Latvijas Universitāte, 2012)
Maģistra darba mērķis izpētīt Latvijas tranzīta pārvadājumu pakalpojumu nozari un tās infrastruktūras nodrošinājumu kā vienu no galvenajiem ietekmējošiem faktoriem, izstrādāt priekšlikumus tranzīta politikas pilnveidošanai Latvijā. Darba teorētiskajā daļā autore noskaidro tranzīta jēdzienu, tranzīta nozīmi tautsaimniecībā un infrastruktūras vērtēšanas kritērijus. Darba otrajā nodaļā autore raksturo Latvijas ekonomisko integrāciju starptautiskajā tirdzniecībā un mainīgo ekonomisko apstākļu ietekmē notikušās pārmaiņas tranzīta pakalpojumu nozarē kopumā un atsevišķi pa transporta veidiem. Darba trešajā nodaļā tiek vērtēta Latvijas tranzīta pārvadājumu pakalpojumu attīstība infrastruktūras kontekstā, izvērtējot infrastruktūras pašreizējo situāciju un finansu pieejamību. Nobeigumā autore izsaka priekšlikumus tranzīta nozares uzlabošanai Latvijā.

The aim of the Master’s Paper is to carry out a research in the branch of transit transportation services in Latvia as well as to examine its infrastructural development as one of the key influencing factors. In addition, the aim of the paper is to put forward the suggestions for the development of the policy of transit transportation in Latvia. In the theoretical part of the paper the author defines the term of transit, describes how the transit influences economics of the country and describes the assessment criteria of the infrastructure. In the second part of the paper the author tackles the issue of economic integration of Latvia in international trade. Besides, the author describes the changes that have taken place under the influence of changing economic conditions. The changes are described generally as well as addressing each kind of transport specifically. In the third part of the paper the author assesses the general development of transit transportation services in Latvia in terms of infrastructure and the access to finances. In the last part of the paper the author puts forward the suggestions for the future development of transit transportation services in Latvia.
Latvian transportation service development perspective inclunding Russian participation in WTO
Keywords: Vadībzinātne